Sudden gains in the outpatient treatment of anorexia nervosa: A process‐outcome study. Issue 10 (26th August 2017) - Cartwright, Anna; Cheng, Yat Ping; Schmidt, Ulrike; Landau, Sabine
Abstract: Objective: Sudden gains (SGs), broadly defined as sudden symptom reductions occurring between two consecutive treatment sessions, have been associated with improved treatment outcomes in anxiety and depression. The present study is the first to formally define SGs in anorexia nervosa and explore the characteristics, demographic and baseline clinical predictors, and clinical impact of SGs in anorexia nervosa. Method: This is a secondary analysis of data from 89 outpatients with broadly defined anorexia nervosa who received one of two psychotherapeutic interventions as part of the MOSAIC trial (Schmidt et al., 2015). SGs were defined using session‐by‐session body mass index (BMI) measures. This study investigated whether SGs were associated with changes in BMI, eating disorder symptomology, general psychopathology, and psychosocial impairment between baseline and 6, 12, and 24 months follow‐up. Results: SGs, experienced by 61.8% of patients, mostly occurred during the early and middle phases of treatment. A larger proportion of SGs predicted larger increases in BMI between baseline and 6, 12, and 24 months follow‐up. Amongst those experiencing at least one SG, fewer days between baseline and a patient's first SG predicted a larger increase in BMI between baseline and both 6 and 12 months follow‐up. The proportion and timing of SGs did not predict changes in other outcome measures. Discussion: SGs in BMI during the outpatient treatment of anorexia nervosa are clinically useful predictors of longer‐term weight outcomes.